The antecedence of financial well-being: insights from financial behavior, attitude, and knowledge among Indonesian youth - Ana Liana; Wendy Wendy; Giriati Giriati (Lembaga Riset Mutiara Akbar (LARISMA), 2026)
This study aims to examine the determinants of financial well-being among young Indonesians by analyzing the direct influence of financial behavior, financial attitudes, and financial knowledge. This study involved 348 respondents aged 20 to 34 years who participated by completing a questionnaire using a Likert scale with a value range of 1 to 7. Data analysis was conducted using WarpPLS 8.0 software. The results showed that financial behavior, financial attitudes, and financial knowledge have a positive and significant effect on financial well-being. This finding strengthens the relevance of behavioral finance theory and confirms that financial intelligence plays a significant role in determining the level of financial well-being of young individuals. Therefore, this study emphasizes the importance of planning and implementing comprehensive financial education to improve the financial well-being of young people in the digital era.